Recreating a unique early modern beer - Flavin, Susan (My University, 2022)
Beer was an important source of nutrition in the past. To study its importance in diet, the nutritional input of beer in early modern Ireland (c1550 – c1650) was examined. Archival records in Dublin Castle facilitated ingredients and recipes of the time to recreate an Irish beer. As well as barley, Irish beer included oats, and hops. A beer was made following the original recipe and ingredients. A working Tudor brewery that used traditional equipment and processes was built at the Weald & Downland Living Museum in Sussex. To select the most appropriate yeast, two strains from the NCYC collection were screened to represent the ancestral strain. The fermentation process was monitored and the beer analysed for nutritional parameters.
Microbiology Society
Keywords: Making Ireland; History